2014
DOI: 10.5551/jat.24109
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamic Effects of Cilostazol Versus Clopidogrel in Stented Patients under Proton Pump Inhibitor Co-administration: The ACCEL-PARAZOL Study

Abstract: Aim: Proton pump inhibitor (PPI) therapy has been shown to attenuate the antiplatelet effects of clopidogrel. The aim of this study was to compare the antiplatelet effects of cilostazol versus clopidogrel in patients co-administered a PPI. Methods: We enrolled PPI-naïve stented patients treated with standard clopidogrel and aspirin therapy for at least six months (n = 100). The patients were randomly assigned to receive either cilostazol at a dose of 100 mg twice daily (CILO group) or clopidogrel at a dose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Cilostazol is a dual inhibitor of PDE3 and adenosine reuptake that may have an important role in reducing ischemic events associated with CAD [ 50 - 53 ]. Cilostazol is a widely used selective and reversible PDE3 inhibitor, which is highly expressed in myocardial and vascular smooth muscle cells (VSMCs) and platelets.…”
Section: Clinical Evidences Of Antiplatelet Regimen In Diabetes Mellimentioning
confidence: 99%
See 1 more Smart Citation
“…Cilostazol is a dual inhibitor of PDE3 and adenosine reuptake that may have an important role in reducing ischemic events associated with CAD [ 50 - 53 ]. Cilostazol is a widely used selective and reversible PDE3 inhibitor, which is highly expressed in myocardial and vascular smooth muscle cells (VSMCs) and platelets.…”
Section: Clinical Evidences Of Antiplatelet Regimen In Diabetes Mellimentioning
confidence: 99%
“…In the Adjunctive Cilostazol versus double-dose ClopidogrEL in Diabetes Mellitus (ACCEL-DM) trial, adjunctive cilostazol to DAPT showed the greater inhibition of platelet aggregation and the lower prevalence of HPR than double-dose clopidogrel in type 2 diabetic patients undergoing PCI [ 50 ]. More interestingly, compared with clopidogrel (75 mg daily) on top of aspirin, adjunctive cilostazol (100 mg twice daily) to aspirin showed the similar inhibition of ADP-induced platelet aggregation [ 52 , 53 ]. In addition, the cilostazol treatment achieved the lower level of platelet function after the stimuli with collagen and arachidonic acid compared with the clopidogrel treatment, which implicates the unique character of antiplatelet effect by cilostazol.…”
Section: Clinical Evidences Of Antiplatelet Regimen In Diabetes Mellimentioning
confidence: 99%
“…44 Interestingly, during proton pump inhibitor coadministration (eg, lansoprazole), cilostazol treatment was shown to achieve a more favorable profile in platelet function than clopidogrel treatment. 45 The relative bioavailability of the 100-mg cilostazol tablet vs an oral 100-mg cilostazol suspension is 100%. The 50-mg twice-daily and 100-mg once-daily tablet dosings are deemed bioequivalent.…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…Aspirin coadministration does not cause clinically significant changes in the coagulation profile, platelet aggregation, or plasma levels of cilostazol and its 2 active metabolites 44 . Interestingly, during proton pump inhibitor coadministration (eg, lansoprazole), cilostazol treatment was shown to achieve a more favorable profile in platelet function than clopidogrel treatment 45 …”
Section: Pharmacokineticsmentioning
confidence: 99%